车辆电动静液压主动悬架系统的设计与试验研究 - 寇发荣 (Jixie chuandong)
A active suspension system with EHA（Electro-Hydrostatic Actuator） is developed to improve the ride comfort performance using a fuzzy PID control scheme,which makes the control system more intelligent.The performance of the controller can be improved by the combination of fuzzy control and PID control.The fuzzy PID EHA active suspension with the core of the DSPIC30F6010 is designed on the base of a simulation of the l/4 vehicle model.Physical prototype of EHA active suspension and test system are developed.The relationship curve between EHA control force and PWM duty ratio is established.The fuzzy PID control test results show that the EHA active suspension system has a good performance under the input of certain signals and thecontrol1er can improve the vehicle ride comfort characteristics by reducing vibration and interference.